2019
DOI: 10.1016/j.jcol.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-care of elderly people with ostomy by colorectal cancer

Abstract: Objective  To identify in literature the scientific production about self-care in elderly people with ostomies by colorectal cancer. Method  Integrative review, performed with the descriptors “self-care”, “ostomy” and “elderly/aged” with the Boolean operator AND in the following databases: SCOPUS, CINAHL, MEDLINE, LILACS and COCHRANE. For the theoretical basis, Orem's Self-Care Deficit Theory was used. Results  A total of 533 papers were found, however, after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
11
0
5
Order By: Relevance
“…[ 43 ] In addition, the patient's level of adaptation is significantly related to self-care ability, because self-care with the help of healthcare workers can help colostomy patients make necessary daily and social adjustments, thereby building self-confidence and social relationships. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 43 ] In addition, the patient's level of adaptation is significantly related to self-care ability, because self-care with the help of healthcare workers can help colostomy patients make necessary daily and social adjustments, thereby building self-confidence and social relationships. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivors are more likely to report financial difficulties than the general population, which results in patients with less adaptability in terms of postoperative social relations, disease recovery, and medical burden [42] The adaptation level of patients with a stoma more than 1 year after surgery was significantly higher than that of patients within 1 year after operation, which may be related to the patient's need for sufficient time to recover and overcome the physical changes brought about by the operation, spiritual trauma, and recovery of family and social life [43] . In addition, the patient's level of adaptation is significantly related to self-care ability, because self-care with the help of healthcare workers can help colostomy patients make necessary daily and social adjustments, thereby building self-confidence and social relationships [44] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurse, as a part of the multiprofessional health team, has the duty of managing the care of elderly people with an intestinal ostomy, from any levels of assistance, from the diagnosis process to home monitoring [ 36 ]. Nurses are required to be adequately prepared with a sufficient theoretical knowledge base which guides their clinical practices [ 37 ] and provision of comprehensive nursing care to older adults [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review study conducted on a sample of 16 studies, whose analysis confirmed that the nurse is one of the professionals closest to the person with a stoma and his family, must act, especially when dealing with the elderly person, as a link between the patient, the family, and the multi-professional health team. In this sense, health professionals, especially the nurse, must be able and competent in assisting the various demands for the care of this population segment so that the actions are active, resolute, and, above all, fully humanized, aiming at improving the quality of life 25 .…”
Section: Discussionmentioning
confidence: 99%